1997
DOI: 10.1109/71.584093
|View full text |Cite
|
Sign up to set email alerts
|

Fault-tolerance through scheduling of aperiodic tasks in hard real-time multiprocessor systems

Abstract: Real-time systems are being increasingly used in several applications which are time critical in nature. Fault-tolerance is an important requirement of such systems, due to the catastrophic consequences of not tolerating faults. In this paper, we study a scheme that provides fault-tolerance through scheduling in real-time multiprocessor systems. We schedule multiple copies of dynamic, aperiodic, nonpreemptive tasks in the system, and use two techniques that we call deallocation and overloading to achieve high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
167
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(169 citation statements)
references
References 26 publications
(33 reference statements)
0
167
0
2
Order By: Relevance
“…In PB-overloading primary of a task is scheduled onto the same or overlapping time slot with the backup of another task on a processor. While in BB-overloading backups of multiple tasks are scheduled onto the same or overlapping time slot on a processor [43]. Since PB-overloading can assign an earlier start time than that of the BB-overloading, thus increasing the schedulability In [44], R. Al-Omari et al concluded that the PB-overloading is able to achieve better performance than BB-overloading, and BB-overloading algorithm is better than no-overloading.…”
Section: Primary Backup Vs Backup Backup Overloading Replicationmentioning
confidence: 99%
“…In PB-overloading primary of a task is scheduled onto the same or overlapping time slot with the backup of another task on a processor. While in BB-overloading backups of multiple tasks are scheduled onto the same or overlapping time slot on a processor [43]. Since PB-overloading can assign an earlier start time than that of the BB-overloading, thus increasing the schedulability In [44], R. Al-Omari et al concluded that the PB-overloading is able to achieve better performance than BB-overloading, and BB-overloading algorithm is better than no-overloading.…”
Section: Primary Backup Vs Backup Backup Overloading Replicationmentioning
confidence: 99%
“…It can be shown that the method from [GMM97] does not work for arbitrary release times. Our general approach is similar to those in the previous section.…”
Section: Hidden ∆-Faultsmentioning
confidence: 99%
“…Recall that, as in [GMM97], we assume that ∆ ≥ 2p max . As in the previous section, the idea is to show that only some special fault sequences, the cruel fault sequence for GAP ∆ need to be considered.…”
Section: Exposed ∆-Faultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall that, as in (Ghosh et al 1997), we assume that Δ ≥ 2p max . We give a linear-time algorithm for testing fault-tolerance in this model in the case of exposed faults.…”
Section: Exposed δ-Faultsmentioning
confidence: 99%